Effect of different feed-rate in bone drilling: experimental and numerical study - Fernandes, M.G.A. (2016)
The behaviour of bone tissue during drilling has been subject of recent studies due to its great importance. Because of thermal nature of the bone drilling, high temperatures and thermal mechanical stresses are developed during drilling that affect the process quality. However, there is still a lack information with regard to the distribution of mechanical and thermal stresses during bone drilling. The present paper describes a sequentially coupled thermal-stress analysis to assess the mechanical and thermal stress distribution during bone drilling. A three-dimensional thermo-mechanical model was developed using the ANSYS/LSDYNA finite element code under different drilling conditions. The model incorporates the dynamic characteristics of drilling process, as well as the thermo-mechanical properties of the involved materials. Experimental tests with polyurethane foam materials were also carried out. It was concluded that the use of higher feed-rates lead to a decrease of normal stresses and strains in the foam materials. The experimental and numerical results were compared and showed good agreement. The proposed numerical model could be used to predict the better drilling parameters and minimize the bone injuries.